Online Shop Entrepreneurship Soul Analysis to Improve The Creativity of Accounting Education Students Muhammadiyah Surakarta University in The Millennial Era - Wijayanti, Susi; Rohmah, Wafrotur (Universitas Muhammadiyah Surakarta, 2023)
Becoming an entrepreneur among students is indeed important, because by deciding to become an entrepreneur students will also reduce the unemployment rate in Indonesia after completing their studies. Entrepreneurs in Indonesia are still at 3.47% and that is still quite low compared to entrepreneurs from other countries. The purpose of this study is to find out how much students have an entrepreneurial spirit and increase their creativity in the millennial era. This study uses qualitative research with informants who are still actively studying at the Muhammadiyah University of Surakarta and have an online shop entrepreneur. The results of this study, students choose to do online entrepreneurship because they want to create their own jobs that are not bound by companies, and can increase their creativity through online shop entrepreneurship. Starting an entrepreneur must also have strong intentions and determination because if they stop in the middle of the road, they will think again and remember the goals to be achieved. To increase their creativity, students can do this by thinking of new interesting ideas, broadening their horizons, and creating attractive promotional strategies. In this millennial era, technology has also become increasingly sophisticated, making it easier for students to take advantage of technology in online entrepreneurship. To increase their creativity, students can do this by thinking of new interesting ideas, broadening their horizons, and creating attractive promotional strategies. In this millennial era, technology has also become increasingly sophisticated, making it easier for students to take advantage of technology in online entrepreneurship. To increase their creativity, students can do this by thinking of new interesting ideas, broadening their horizons, and creating attractive promotional strategies. In this millennial era, technology has also become increasingly sophisticated, making it easier for students to take advantage of technology in online entrepreneurship.